Estampagem a quente em escala piloto - Júlio Henrique de Araújo Rosa (2015)
In recent years, world efforts in research and development of hot stamped products for application in the automotive industry have been growing. The increasing demands of this industry for reductions in the vehicle weight and increased passenger safety have resulted in the growing use of steels with high mechanical strength. For steels with a given chemical composition, the highest value of tensile strength can be obtained when the microstructure is fully martensitic. The application of this condition in steel structural parts and reinforcements has been demonstrated as an alternative for the automobile industry to meet the seemingly contradictory requirements and increasingly stringent fuel consumption and passenger safety in a collision. The process of hot forming steel followed by quenching (the so called hot stamping) is an option in the manufacture of parts for the vehicle structure displaying a tensile strength exceeding 1500 MPa and with minimum springback after forming. The trend towards hot forming for the manufacture of a growing number of automotive parts of the structure does not happen just in the most industrialized countries. The auto parts manufacturers in Brazil are also investing in new production lines for this process, demanding an increasing amount of steel for this application. In this context, this work has as main objective to characterize the microstructure of steel 22MnB5 hot stamped by using a pilot equipment.